2019
DOI: 10.1007/s10888-018-9404-z
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality and well-being in the U.S.: evidence of geographic-scale- and measure-dependence

Abstract: Income Inequality and Well-Being in the U.S.: Evidence of Geographic-Scale-and Measure-Dependence U.S. income inequality has risen dramatically in recent decades. Researchers consistently find that greater income inequality measured at the state or national level is associated with diminished subjective well-being (SWB) in the U.S. We conduct the first multi-scale analysis (i.e., at the ZIP-code, MSA, and state levels) of the inequality-SWB relationship using SWB data from the U.S. Gallup Healthways Well-Being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…American states set their own tax policies. Measuring income inequality at the state level is a common practice for studying various outcomes, including life satisfaction (Ahn et al 2016; Ifcher, Zarghamee, and Graham 2019). However, happiness is an individual property that varies from person to person, and one’s relative position in an inequality system via social comparison should not be ignored.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…American states set their own tax policies. Measuring income inequality at the state level is a common practice for studying various outcomes, including life satisfaction (Ahn et al 2016; Ifcher, Zarghamee, and Graham 2019). However, happiness is an individual property that varies from person to person, and one’s relative position in an inequality system via social comparison should not be ignored.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Thus, it is important that researchers consider what level of inequality they are interested in examining and operationalize their measures accordingly. This operationalization of the level of analysis, we argue, has important theoretical and empirical implications that researchers assessing perceptions of inequality need to consider (e.g., Ifcher, Zarghamee, & Graham, 2019;Newman, Shah, & Lauterbach, 2018;Xu & Garand, 2010).…”
Section: What Level Of Analysis?mentioning
confidence: 99%
“…Prior research finds inconsistent effects on the outcomes of higher economic inequality. While initial studies found a negative effect of economic inequality on subjective well-being [4][5][6] , subsequent work did not corroborate these results [7][8][9] , with a recent metaanalysis finding no statistically significant relationship between economic inequality and subjective well-being 10 . Similarly, while initial studies found that higher economic inequality is associated with worse health outcomes 11,12 , subsequent research has not found consistent support 13,14 .…”
mentioning
confidence: 90%